STP-based marketing strategy in Paper Mill Industry: A Case Study of expansion from East Java to Jabodetabek - Nursasi, Farika; Sari, Karina Kemala; Sudarmiatin; Wijijayanti, Trisetia (PT Maju Malaqbi Makkarana, 2025)
This study aims to analyze the application of STP-based marketing strategies (Segmenting, Targeting, Positioning) in paper mill companies engaged in the production and sale of Paper Core and Paper Tube, in the context of market expansion from East Java to the Greater Jakarta area. This case study uses a qualitative descriptive approach by collecting data through in-depth interviews, observations, and documentation of the company's marketing activities. The results of the study show that implementing the STP strategy plays a significant role in expanding market reach and increasing companies' competitiveness. Market segmentation is based on geographical variables, industry demographics, and customer behavior, leading the company to target the textile, plastic film, and packaging industries in the Greater Jakarta area. The targeting strategy is focused on medium and large industrial segments with high product quality needs and fast delivery services. In terms of positioning, the company positions itself as a